The Impact of Glucose-Lowering Drugs on Sarcopenia in Type 2 Diabetes: Current Evidence and Underlying Mechanisms - Elena Massimino; Anna Izzo; Gabriele Riccardi; Giuseppe Della Pepa (Cells, 2021)
The age-related decrease in skeletal muscle mass together with the loss of muscle power and function is defined sarcopenia. Mounting evidence suggests that the prevalence of sarcopenia is higher in patients with type 2 diabetes mellitus (T2DM), and different mechanisms may be responsible for this association such as impaired insulin sensitivity, chronic hyperglycemia, advanced glycosylation end products, subclinical inflammation, microvascular and macrovascular complications. Glucose-lowering drugs prescribed for patients with T2DM might impact on these mechanisms leading to harmful or beneficial effect on skeletal muscle. Importantly, beyond their glucose-lowering effects, glucose-lowering drugs may affect per se the equilibrium between protein anabolism and catabolism through several mechanisms involved in skeletal muscle physiology, contributing to sarcopenia. The aim of this narrative review is to provide an update on the effects of glucose-lowering drugs on sarcopenia in individuals with T2DM, focusing on the parameters used to define sarcopenia: muscle strength (evaluated by handgrip strength), muscle quantity/quality (evaluated by appendicular lean mass or skeletal muscle mass and their indexes), and physical performance (evaluated by gait speed or short physical performance battery). Furthermore, we also describe the plausible mechanisms by which glucose-lowering drugs may impact on sarcopenia.